Asymmetric arbitrage trading on offshore and onshore renminbi markets - Sercan Eraslan (Deutsche Bundesbank, 2017)
This paper investigates the asymmetries in arbitrage trading with onshore and offshore renminbi spot rates, focusing on the time-varying driving factors behind the deviations of the two rates from their long-run equilibrium. Fundamentally, offshore and onshore renminbi rates represent the same economic quantity and hence should be driven by the same pricing mechanism. However, the two exchange rates deviate remarkably from each other, creating arbitrage opportunities over many days. For the empirical analysis, I build a three-regime threshold vector error correction model with offshore and onshore spot rates and further regime-dependent explanatory variables. The model is estimated in different periods in order to consider the impact of appreciation and depreciation expectations on possible arbitrage trading. The estimation results suggest that directional expectations, global risk sentiment, and local as well as global liquidity conditions dominate the adjustment process in the absence of arbitrage trading when the offshore rate is stronger than its onshore counterpart. However, the error correction mechanism of the offshore (onshore) rate toward its equilibrium with the onshore (offshore) rate is driven by the arbitrage trading due to a relatively weaker (stronger) offshore (onshore) rate in the upper regime in times of appreciation (depreciation) expectations.
Keywords: C32; F31; G15; 330; threshold cointegration; vector error correction model; arbitrage trading; renminbi exchange rates; onshore and offshore markets